The effect of fermentor temperatures and moisture content of substrate on the nutritive value of fermented palm oil sludge - Sinurat, A.P.; Purwadaria, T.; Rosida, J.; Surachman, H.; Hamid, H.; Kompiang, P. (Indonesian Animal Sciences Society, 1998)
A series of experiment was designed in order to improve the nutritive value of palm oil sludge (POS) through fermentation. POS was fermented in a fermentor chamber with different temperatures (28 and 32oC) and initial moisture content of the substrate (50,55 and 60%). The nutrient content (crude protein, true protein, in vitro- dry matter and protein digestibility and crude fibre) of the fermented products were evaluated at different stages of the fermentation, i.e.: before incubated (F0), 3 d after aerobic incubation (F3) and 2 d anaerobic incubation after F3 (EN). Cellulase and mannanase activity of the EN products were also measured before and after dried at 60oC. Fermentation at 32oC produced better product (higher nutritive values), although the in vitro dry matter digestibility was not affected by the temperatures. All parameters measured were not significantly influenced by the initial moisture content of the substrate. The nutritive value of unincubated POS (F0) was significantly poorer than the F3 and EN and there was no different in nutrient value between F3 and EN. Soluble nitrogen and in vitro dry matter digestibility were not significantly affected by the stages of the fermentation. Mannanase activity in the EN product was significantly higher when the fermentation was performed at 32oC than those at 28oC and the enzyme activity was reduced after dried (320.7 vs 201.8 U/g DM). The cellulase activity of the fresh/wet fermented product produced at 28oC was significantly higher than those produced at 32oC, but the reverse was occurred in the dry products. It is concluded that fermentation process of palm oil sludge at 32oC and initial moisture content of 50-60% produced better (in vitro) nutritive value. Key words: Palm oil sludge, fermentation, nutritive value